Micro-foundations of producer power in Colombia and the Philippines: Towards a political understanding of rents - Charmaine G. Ramos (University of Bath, Centre for Development Studies (CDS), 2015)
This paper examines rent-creating state interventions in Colombia and the Philippines, where the authority to mobilise agricultural levies collected from leading agro-export sectors were delegated to producer associations. It investigates why coffee levies in Colombia are associated with production and welfare-enhancing outcomes, while coconut levies in the Philippines are depicted as non-developmental rent capture. The paper forwards an explanation based on a comparison of the basis in political economy of the power exercised by the leading sectoral organisations, FEDECAFE in Colombia and COCOFED in the Philippines. It finds that variations in historical political economy mean that conditions for collective action and the exercise of political power to influence rent mobilisation for developmental purposes were more robust for Colombian coffee than Philippine coconut producers. This paper explains the variations in terms of: (1) the economic basis of the power exercised by the producers; (2) the historical basis of productive expansion in the sectors; and (3) the political basis of the collection and mobilisation of the levies.
Keywords: 330; political economy; institutions; rent-seeking; agro-export commodity production; producer associations